Womanpower in the 1960's, Fabian Feminism. - Beals, Polly (2009)
Worked on book about Fabian feminism. Finished the final chapter but book isn't complete yet. Wrote and delivered paper in London in March 2009. Is expanding book to include 1980's and 1990's Fabian feminism.
Keywords: dept.his; faculty_collection; sabbatical_report

Eighteenth-Century Russia. - Chrissidis, Nikolaos (2008)
Worked on a book and wrote and presented several paper on eighteenth century Russia.
Keywords: dept.his; faculty_collection; sabbatical_report

American Social Credit Movement. - Kalk, Bruce H. (2006)
Keywords: dept.his; faculty_collection; sabbatical_report

When France was King of 'Kartographie' - Petto, Christine Marie (2005)
Keywords: dept.his; faculty_collection; sabbatical_report

Northern Treasures and Southern Essences, an Exploration of Vietnamese Traditional Medicine. - Thompson, C. Michele (2004)
Keywords: dept.his; faculty_collection; sabbatical_report

The System: The American Constitution in Historical Perspective 1763-1929 - Gerber, Richard A. (Cengage Learning, 2009)
Keywords: United States; United States. Constitution; Constitutional history; dept.his; faculty_collection

Revolution and Union: The American Dilemma 1763-1877 - Gerber, Richard A. (Cengage Learning, 2008)
Keywords: History; Textbooks; United States; dept.his; faculty_collection

The Civil Rights Act of 1875: A Reexamination - Gerber, Richard A.; Friedlander, Alan (Connecticut Academy of Arts and Sciences, 2008)
Keywords: Civil rights; History; History; African Americans; United States; dept.his; faculty_collection

Not Your (founding) Fathers' Constitution: Teaching United States Constitutional History - Gerber, Richard A. (The Connecticut Urban Consortium ; New Haven Public Schools, 2007)
Synopsis of the lectures presented during the three-year program, together with a PowerPoint presentations on CD-ROM. This material can be used for preparation of classroom instructional program or directly in the classroom.
Keywords: History; Study and teaching; Study and teaching; Constitutional history; United States. Constitution; United States; United States; dept.his; faculty_collection

When France Was King of Cartography: The Patronage and Production of Maps in Early Modern France - Petto, Christine Marie (Lexington Books, 2007)
When France Was King of Cartography investigates over a thousand maps and nearly two dozen map producers, analyzes the map as a cultural artifact, map producers as a group, and the array of map viewers over the course of two centuries in France. The book focuses on situated knowledge or 'localized' interests reflected in these geographical productions. Through the lens of mapmaking, it examines the relationship between power and the practice of patronage, geography, and commerce in early modern France.
SCSU Faculty Scholar Award
Keywords: 17th century; Cartography; 17th century; Map industry and trade; 18th century; 18th century; Map industry and trade; Cartography; France; History; SCSU Faculty Scholar Award; award_winner; dept.his

Crisis of the Black Intellectual - Wright, W. D. (Third World Press, 2007)
Keywords: African American intellectuals; African Americans; Intellectual life; dept.his; faculty_collection

Black History and Black Identity: A Call for a New Historiography - Wright, W. D. (Praeger, 2002)
Keywords: African Americans; Historiography; African Americans; Race identity; dept.his; faculty_collection

The Origins of the Southern Strategy: Two-Party Competition in South Carolina, 1950-1972 - Kalk, Bruce H. (Lexington Books, 2001)
Keywords: 1951-; 20th century; South Carolina; History; Political parties; Politics and government; South Carolina; dept.his; faculty_collection

The Hammer of the Inquisitors: Brother Bernard Délicieux and the Struggle Against the Inquisition in Fourteenth-Century France - Friedlander, Alan (Brill, 2000)
Keywords: Bernard; Délicieux; frère; approximately 1260-approximately 1320; Franciscans; Biography; Inquisition; Church history; France; Languedoc; Languedoc; Languedoc (France); dept.his; faculty_collection

Competitive hagiography in biographies of al-Awzā'ī and Sufyān al-Thawrī - Judd, S.C. (Journal of the American Oriental Society, 2002)
The present paper examines how followers of 'Abd al-Rahcombining dot belowmān b. 'Amr al-Awzā'ī and Sufyān al-Thawrī tried to create boundaries between the nascent madhhabs that claimed them as eponyms. In the absence of significant differences in legal method, students turned to the two shaykhs' responses to the 'Abbāsid revolution to draw distinctions between them. The Arabic biographical sources contain stories of their responses to the revolution that reveal a dialogue between followers of the two shaykhs about the relative merits of their choices. The changing interpretations of their attitudes toward the 'Abbāsid regime and the exaggeration evident in the anecdotes examined have significant implications for our reading of medieval Arabic biographical sources.
1 citations (Crossref) [2023-10-31]
Keywords: dept.his

From l'état, c'est moi to l'état, c'est l'état: Mapping in early modern France - Petto, C.M. (Cartographica, 2005)
Using the printed works of two French cartographers, Alexis-Hubert Jaillot and Guillaume Delisle, I investigate how the changing interests of the government directed not only the process of map-making but the rhetoric evident in printed maps and atlases. Jaillot, a commercial map publisher flourishing during the second half of the seventeenth century, produced maps that participated in the fabrication of the image of Louis XIV. Maps served this "cult of image" and contributed to a multimedia show to glorify the reign of the Sun King and to support his personal state - l'état, c'est moi. In the eighteenth century, while a rhetoric of image was still present on printed maps, the "cult of image" was dead and mapping appealed to the rise of the impersonal or bureaucratized state - l'état, c'est l'état. Delisle produced maps as instruments of statecraft that aided the state in furthering its domestic and international interests. In particular, printed maps of the Americas served the government's need to acquire greater territorial control. While images were still powerful on New World maps, the French boundary claims, egregious to some, if uncontested could be produced time and again as a true representation and legitimization of territorial control.
4 citations (Crossref) [2023-10-31]
Keywords: Cartography; France; History; Image; Louis XIV; Printed maps; Rhetoric; Scientific authority; dept.his; eighteenth century; historical cartography; mapping method; territorial delimitation

In defense of homology and history: A response to Allen - Paddock, T. (Philosophy and Geography, 2004)
0 citations (Crossref) [2023-10-31]
Keywords: dept.his

"I should not be wearing a pilgrim hat": Making an Indian place in urban schools, 1945-75 - Amerman, S. (American Indian Culture and Research Journal, 2007)
2 citations (Crossref) [2023-10-31]
Keywords: dept.his

Playing the feminine card: Women of the early modern map trade - Petto, C.M. (Cartographica, 2009)
Images of allegorical women have often appeared on maps or in atlas frontispieces as objects in need of security provided by male protectors or as the counterpoint, objects to be dominated by male possessors. Exploring the role of women in the early modern map trade initially reveals not only a similar male dominance but also similar calls for protection. Nearly 10 years ago, Alice Hudson and Mary McMichael Ritzlin produced a checklist of about 300 pre-twentieth-century women in cartography. The present work contributes to the further investigation of some of these women in the early modern map trade and studies in the allied field of book printing, and more general works on women in commercial trade provide the framework for this piece. Women in the map trade were quite cognizant of the challenges of their gender and used a feminine discourse-that is, they played the feminine card-when it served their interests. All of these women, however, participated in the male discourse of the corporate community, which entailed not only making contracts and partnerships and advertising and producing new works but also making use of the social network within the trade, as well as exploiting the patronage connections cultivated by their husbands before them.
5 citations (Crossref) [2023-10-31]
Keywords: Angleterre; England; France; commerce de l'impression des cartes; dept.his; engravers; femmes; graveurs; image; map publishers; map-printing trade; women; éditeurs cartographiques

The great industrial war: Framing class conflict in the media, 1865-1950 - Rondinone, T. (Rutgers University Press, 2009)
The Great Industrial War, a comprehensive assessment of how class has been interpreted by the media in American history, documents the rise and fall of a frightening concept: industrial war. Moving beyond the standard account of labor conflict as struggles between workers and management, Troy Rondinone asks why Americans viewed big strikes as "battles" in "irrepressible conflict" between the armies of capital and laborùa terrifying clash between workers, strikebreakers, police, and soldiers.Examining how the mainstream press along with the writings of a select group of influential reformers and politicians framed strike news, Rondinone argues that the Civil War, coming on the cusp of a revolution in industrial productivity, offered a gruesome, indelible model for national conflict. He follows the heated discourse on class war through the nineteenth century until its general dissipation in the mid-twentieth century. Incorporating labor history, cultural studies, linguistic anthropology, and sociology, The Great Industrial War explores the influence of historical experience on popular perceptions of social order and class conflict and provides a reinterpretation of the origins and meaning of the Taft-Hartley Act and the industrial relations regime it supported. copyright © 2010 by Troy Rondinone All rights reserved.
Journal Abbreviation: The Gt. Indust. War: Framing Cl. Confl ict in the Media, 1865-1950 Pages: 247 Publication Title: The Gt. Indust. War: Framing Cl. Confl ict in the Media, 1865-1950
Keywords: dept.his

Reconstructing meaning in Deuteronomy 22:5: Gender, society, and transvestitism in Israel and the ancient Near East - Vedeler, H.T. (Journal of Biblical Literature, 2008)
4 citations (Crossref) [2023-10-31]
Keywords: dept.his

Land makes the man: topography and national character in german school books - Paddock, Troy R. E. (Lived topographies and their mediational forces, 2005)
"This collection explores the various forms of narrative, semiotic, and technological mediation that shape the experience of place. From the East End of London to Navajo lands to Ground Zero, Lived Topographies examines the great effect of language, mass media, surveillance, and other incursions of the contemporary world on topographical experience and description. Gary Backhaus and John Murungi have assembled a wide array of scholars to provide an interdisciplinary approach to this subject, giving this collection a unique perspective on the phenomenology of place."–Jacket.
OCLC: 57557650
Keywords: dept.his

Chronoscapes/chronos escapes: a meditation on historical time - Paddock, Troy R. E. (Ecoscapes: geographical patternings of relations, 2006)
OCLC: 62493042
Keywords: dept.his

Is one world enough for all of us?: Thoughts on globalization - Paddock, Troy R. E. (Dangers in the incommensurability of globalization: socio-political volatilities, 2008)
OCLC: 1062216027
Keywords: dept.his

A Call to Arms: Propaganda, Public Opinion, and Newspapers in the Great War - Paddock, Troy R. E. (Praeger Publishers, 2004)
World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t., World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t
Keywords: Press coverage; Propaganda; World War; 1914-1918; Public opinion; Press and propaganda; War; World War; 1914-1918; dept.his; faculty_collection

'Truth Systematised’: The Changing Debate over Slavery and Abolition - Forbes, Robert P. (Prophets of Protest: Reconsidering the History of American Abolitionism, 2006)
The first collection of original contributions on American abolitionism to appear in a generation.The campaign to abolish slavery in the United States was the most powerful and effective social movement of the nineteenth century and has served as a recurring source of inspiration for every subsequent struggle against injustice. But the abolitionist story has traditionally focused on the evangelical impulses of white, male, middle-class reformers, obscuring the contributions of many African Americans, women, and others.Prophets of Protest, the first collection of writings on abolitionism in more than a generation, draws on an immense new body of research in African American studies, literature, art history, film, law, women's studies, and other disciplines. The book incorporates new thinking on such topics as the role of early black newspapers, anti-slavery poetry, and abolitionists in film and provides new perspectives on familiar figures such as Sojourner Truth, Louisa May Alcott, Frederick Douglass, and John Brown.With contributions from the leading scholars in the field, Prophets of Protest is a long overdue update of one of the central reform movements in America's history.
Keywords: dept.his

The Missouri Controversy and Sectionalism - Forbes, Robert P. (Congress and the Emergence of Sectionalism: From the Missouri Compromise to the Age of Jackson, 2008)
In 1815 the United States was a proud and confident nation. Its second war with England had come to a successful conclusion, and Americans seemed united as never before. The collapse of the Federalist party left the Jeffersonian Republicans in control of virtually all important governmental offices. This period of harmony—what historians once called the Era of Good Feeling—was not illusory, but it was far from stable. One-party government could not persist for long in a vibrant democracy full of ambitious politicians, and sectional harmony was possible only as long as no one addressed the hard issues: slavery, race, western expansion, and economic development.Congress and the Emergence of Sectionalism: From the Missouri Compromise to the Age of Jackson inaugurates a new series for the United States Capitol Historical Society, one that will focus on issues that led to the secession crisis and the Civil War. This first volume examines controversies surrounding sectionalism and the rise of Jacksonian Democracy, placing these sources of conflict in the context of congressional action in the 1820s and 1830s. The essays in this volume consider the plight of American Indians, sectional strife over banking and commerce, emerging issues involving slavery, and the very nature of American democracy.“It is to be regretted that the rich and powerful too often bend the acts of government to their selfish purposes…. There are no necessary evils in government. Its evils exist only in its abuses. If it would confine itself to equal protection, and, as Heaven does its rains, shower its favors alike on the high and the low, the rich and the poor, it would be an unqualified blessing. In the act before me there seems to be a wide and unnecessary departure from these just principles.”—Andrew Jackson, Veto Message Regarding the Bank of the United States, July 10, 1832“I consider, then, the power to annul a law of the United States, assumed by one State, incompatible with the existence of the Union, contradicted expressly by the letter of the Constitution, unauthorized by its spirit, inconsistent with every principle on which it was founded, and destructive of the great object for which it was formed.”—Andrew Jackson, Proclamation Regarding Nullification to the People of South Carolina, December 10, 1832
Keywords: dept.his

The venomous course of southwestern opium: Qing prohibition in Yunnan, Sichuan, and Guizhou in the early nineteenth century - Bello, David (The Journal of Asian Studies, 2003)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-511-721-924-233 tex.type: [object Object]
Keywords: dept.his

Gedachtes wohnen: Heidegger and cultural geography - Paddock, Troy (Philosophy & Geography, 2004)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-707-720-981-012 tex.type: [object Object]
Keywords: cultural geography; dept.his

The historiography of american violence - Leonard, Ira M; Leonard, Christopher C (Homicide Studies, 2003)
Historians have generally agreed that the United States has always been an extremely violent nation; however, since the 1950s they have been myopic in their treatment of violence in America and have not provided the American people with essential information about their society and culture. Those historians who focused on violence in America, until the 1990s, have focused on only one form of violence—collective social violence. Largely overlooked, and equally significant, are interpersonal violence (including criminal and domestic violence) and the effect of war. This deficiency helps explain why Americans seem genuinely at a loss to understand the nature, character, and frequency of violence in America's past and present, especially when a high-profile violent incident occurs. This article surveys the historiography of violence in America through the 1990s and examines the contributions of historians and legal scholars who have focused on interpersonal and criminal violence. © 2003, SAGE Publications. All rights reserved.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/168-886-742-543-29X tex.type: [object Object]
Keywords: dept.his; historiography; lynching; riots; vigilantism

The pennsylvania state equal rights league and the northern black struggle for legal equality, 1864-1877 - Davis, Hugh (Pennsylvania Magazine of History and Biography, 2002)
Citation Key Alias: lens.org/021-378-663-485-819 tex.type: [object Object]
Keywords: dept.his; ⛔ No DOI found

Out of Africa - Feinberg, H.M.; Solodow, J.B. (Journal of African History, 2002)
This article traces the origins of the familiar quotation, 'there is always something new coming out of Africa'. It demonstrates that the phrase was a proverb that originated in Greece no later than the fourth century BC. It charts the transmission of the phrase from Aristotle to the twentieth century, noting that Erasmus is the most important link in the Renaissance and that he may be responsible for the current form in which the phrase is used. The article also shows that the meaning of the phrase was very different in ancient times from what it is today. Whereas 'something new' to Aristotle meant strange hybrid animals, current writers use the phrase with a sense of admiration.
9 citations (Crossref) [2023-10-31]
Keywords: Africa; Historiography; dept.his; dept.wll; history; perception; regional geography

South African territorial segregation: new data on African farm purchases, 1913-1936 - Feinberg, Harvey M; Horn, Andre C (The Journal of African History, 2009)
By using new sources and a complementary historical and geo-analytical approach, this article Illustrates that the Natives Land Act (no. 27 of 1913) failed to stop Africans from buying land. New evidence demonstrates that African land ownership outside the reserves in the Transvaal actually increased after 1913. This evidence leads to a deeper questioning of the extent to which the South African government was able to impose rural territorial segregation by 1936 and reveals the limits of white power in the early Union period.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-862-260-598-682 tex.type: [object Object]
Keywords: Archives; Land; Law; Race; South Africa; apartheid; dept.his; historical geography; land tenure; landownership; legislation; racial segregation

Semblance of Sovereignty: Cartographic Possession in Map Cartouches and Atlas Frontispieces of Early Modern Europe - Petto, Christine M. (Symbolic Landscapes, 2009)
Maps always present an interpretation of reality and always carry distortions, some of which are consciously or unconsciously ideological. The geographicity of mapping, which involves an intertwining of both science and art, is a vehicle for spatialized/spatializing interpretations of an actual spatiality, and as such is a catalyst for enacting further spatial productions on the basis of the capacity of maps to project themselves “into the landscape.” The scientific pretensions of mapping serve to veil the character of their projective enactment. Maps always entail virtual embodiment, that is, maps realize one possibility out of many, even in the most mathematically “accurate” of spatial relations. Thus, if the imaginative involves both embodied schema and virtual embodiments, we cannot dismiss the role of the geography of imagination in a dialectical relation with the geography of perception, of the actual. The symbolic function of cartouches and frontispieces provides an imagineering context of constructing reality on the basis of the symbolization.
Citation Key Alias: lens.org/078-762-124-744-708
Keywords: Facsimile Edition; Manuscript Library; Online Collection; United Province; Virtual Embodiment; dept.his

Guarding the switch: cultivating nationalism during the pullman strike - Rondinone, Troy (The Journal of the Gilded Age and Progressive Era, 2009)
The Pullman Strike of 1894 was a cataclysmic event for the nation. During its violent course, the print media provided an interpretive frame that portrayed the strike in large measure as an immigrant-inspired attack on American laws and democratic customs. Often characterizing the strikers as “foreigners” in the thrall of anarchist ideologies and a tyrannous labor chieftain, journalists painted a stark picture indeed. Employing framing theory, Gramsci's notion of hegemony, and recent insights on the ethnic quality of nationalism, this essay argues that newspapers and other major print periodicals significantly contributed to the formation of nationalist attitudes at a time when many Americans were deeply worried over the direction in which the country was headed. © 2009, Society for Historians of the Gilded Age and Progressive Era. All rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/091-980-600-754-189 tex.type: [object Object]
Keywords: dept.his